VIRTUAL REALITY MUSEUM MULAWARMAN BERBASIS VIDEO 360Â° - Firdaus, Muhammad Bambang; Tejawati, Andi; Budiman, Edy; Wahyudianto, Mochamad Rizky; Anam, M Khairul (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2021)
Recent years, visitors have decreased in the Mulawarman Museum, located in Tenggarong Kutai Kartanegara. A small number of visitors to the Mulawarmen Museum could have been due to a lack of promotions. The purpose of this study is to develop and present the Mulawarman Museum as a promotional medium a Visual Video Application for the Mulawarman Tenggarong Kutai Kartanegara. A combination of VR and Android mobile technology, which is owned by most levels of society, enables application users to view the videos in 360 degrees, can serve this research purpose. The aim of the research is This research. The test results from Android devices show that the application is smooth to run and suitable for use in versions of Android 5.1 and later with a screen-like aspect ratio of 16:9 and 18:9. All of the questions in the questionnaire received agree and strongly agree between 85% and 100%.